2016
DOI: 10.18805/ijar.9495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Poly-herbal mixture and butyric acid feeding on immune parameters of postpartum Murrah buffaloes

Abstract: The present study was conducted in 24 Murrah buffaloes to study the effect of supplementation of poly-herbal mixture and butyric acid with the objective to reduce parturition stress and to improve immunity. In this study, control group i.e T 0 (n=6) was offered ration as per NRC requirement plus 10 % and the rest of three supplemented groups T 1, T 2 and T 3 (n=6 for each group) were offered ration as per control group along with three different supplementations, (T 1 = poly-herbal supplementation for seven da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Chang et al(2011) studied that the antiproliferative effect of steamed ginger at 120 0 C for 4 h was approximately 1.5-2 fold higher than that of dried and fresh ginger. Chandra et al (2016) reported that the effect of poly herbal mixture supplementation on post-partum reproductive performance in Murrah buffaloes. The poly herbal mixture was made by mixing 25 gram each of Foeniculum vulgare (Saunf), Trachyspermum ammi (Ajwain), Trigonella foenumgraecum (Methi), Zingiber officinale (Sundh), Anethum graveolens (Sowa), Elettaria cardamomum (Cardamom) and 25-gram black salt (Kala Namak).…”
Section: Trigonella Foenum-graecum (Methi)mentioning
confidence: 99%
“…Chang et al(2011) studied that the antiproliferative effect of steamed ginger at 120 0 C for 4 h was approximately 1.5-2 fold higher than that of dried and fresh ginger. Chandra et al (2016) reported that the effect of poly herbal mixture supplementation on post-partum reproductive performance in Murrah buffaloes. The poly herbal mixture was made by mixing 25 gram each of Foeniculum vulgare (Saunf), Trachyspermum ammi (Ajwain), Trigonella foenumgraecum (Methi), Zingiber officinale (Sundh), Anethum graveolens (Sowa), Elettaria cardamomum (Cardamom) and 25-gram black salt (Kala Namak).…”
Section: Trigonella Foenum-graecum (Methi)mentioning
confidence: 99%
“…The buffalo holds the distinction of being the world's second most crucial milch animal, contributing to over 95% of the milk production in South Asia (Javaid et al, 2009) [7] . With a continuously growing global buffalo population, estimates surpass 188.33 million, and more than 95% (178.91 million) of this population is concentrated in Asia (FAO STAT, 2019) [4] . In India, the current buffalo population stands at 105.34 million, securing its position as the foremost buffalo-holding country globally.…”
Section: Introductionmentioning
confidence: 99%
“…Ayurveda, rooted in natural remedies and herbal-based approaches, stands out for its ability to minimize side effects, maximize benefits, and reduce health hazards. The incorporation of herbs into livestock management, as highlighted by Chandra S, et al (2017) [4] , presents an avenue for effective growth, reproductive management, and successful animal. The Asparagaceae family is commonly found in low-altitude areas, thriving in shade and tropical climates across Asia, Australia, and Africa.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have been published on the use of natural food additives in animal diets. Many secondary products or plant extracts have been used, such as essential oils, in feeding animals to improve their growth, production and immune responses (Thakare, 2004;Westendarp, 2005;Chandra et al, 2017). It has been observed that there is an antibacterial or antifungal effect in the rumen when using such additives and this improves the utilization of the diet (Wallace, 2004).…”
Section: Introductionmentioning
confidence: 99%